Comprehensive LET reviewer based on NCBTS and Table of Specifications (TOS) : specialization : English : book 1 - Espique, Felina P.; Busbus, Stephenie Lee Ong-; Ayao-Ao, Shirley L.; Ayunon, Bernardita C.; Ferrer, Joselita M.; Soliba, Bernadette L.; Siagto, Geraldine; Copiling, Genevieve (Quezon City : Lorimar Publishing Inc., 2015)
This LET Reviewer is prepared to help you pass the LET. Mind you, not all who take the LET pass it.
1. Remedial Instruction in English -- 2. English for specific purposes -- 3. Language Curriculum for secondary school -- 4. Introduction to linguistics -- 5. Structure of english -- 6. Introduction to stylistics -- 7. Literary Criticism -- 8. Mythology and Folklore -- 9. Afro-Asian Literature (Including, Philippine Literature) -- 10. English and American Literature -- 11. The teaching of speaking, Listening and reading -- 12. Teaching of literature -- 13. Preparation and evaluation of instructional materials -- 14. Language ang literature assessment -- 15. Language Research -- 16. Campus Journalism -- 17. Translation and editing of text -- 18. Speech and stage arts -- 19. Creative Writing.
Includes bibliographical references.
Keywords: TEACHERS -- EXAMINATIONS, QUESTIONS, ETC. -- PHILIPPINES